When Groups of Different Sizes Collide: Effects of Targeted Verbal Aggression on Intragroup Functioning - Klonek, Florian E.; Gerpott, Fabiola H.; Handke, Lisa (Group & organization management, 2023)
When competing for scarce resources, groups can behave aggressively toward one another. Realistic conflict theory suggests that intergroup hostility internally ties groups together, thus improving intragroup functioning. In contrast, conflict spillover theory suggests that aggressive behaviors between groups can permeate to the intragroup level and thus worsen intragroup functioning. We reconcile these two opposite perspectives by introducing the relative group size as a moderator that determines when and how targeted verbal aggression from one group harms or improves intragroup functioning in the targeted group. We tested our hypotheses using a sample of in-situ observations of transcribed plenary discussions in the German national parliament and compared intergroup targeted verbal aggression by distinguishing targeted verbal aggression from two social groups (i.e., a new populist smaller party vs. a larger group of veteran parliament members). We measured targeted verbal aggression as a form of hostile intergroup behavior from each social group using computerized text analyses. We analyzed intragroup functioning using a measure of verbal mimicry. Our results show support for our hypotheses. We discuss theoretical and practical implications for the verbal aggression and intergroup relations literature.
CRIS-Team Scopus Importer:2023-09-18
Keywords: field study; group size; language style matching; parliamentary meetings; verbal aggression; verbal mimicry